A radiofrequency system for in vivo hyperpolarized 13C MRS experiments in mice with a 3T MRI clinical scanner. Issue 6 (5th April 2016) - Giovannetti, Giulio; Flori, Alessandra; Marsigli, Fabio; De Marchi, Daniele; Frijia, Francesca; Giannoni, Massimo; Kusmic, Claudia; Positano, Vincenzo; Aquaro, Giovanni Donato; Menichetti, Luca
Summary: Hyperpolarized carbon‐13 magnetic resonance spectroscopy (MRS) is a powerful tool to explore tissue metabolic state, by permitting the study of intermediary metabolism of biomolecules in vivo . However, a number of technological problems still limit this technology and need innovative solutions. In particular, the low molar concentration of derivate metabolites give rise to low signal‐to‐noise ratio (SNR), which makes the design and development of dedicated radiofrequency (RF) coils a fundamental task. In this article, the authors describe the simulation and the design of a RF coils configuration for MR experiments in mice, constituted by a 1 H whole body volume RF coil for imaging and a 13 C single circular loop surface RF coil for performing 13 C acquisitions. After the building, the RF system was employed in an in vivo experiment in a mouse injected with hyperpolarized [1‐ 13 C]pyruvate by using a 3 T clinical MR scanner. SCANNING 38:710–719, 2016. © 2016 Wiley Periodicals, Inc.